Hak-Hak Pemain Sepak Bola Dalam Penundaan Liga Pada Masa Pandemi Covid-19 - Danial Akta Futaki (Faculty of Law, Universitas Airlangga, 2021)
AbstractCOVID-19 pandemic brought many impacts to every sector around the world, football is one of them. As a modern industry, the relation between professional football players and professional football clubs is a working relation that produces rights and responsibility for both parties that already agree on the contract. Problems occur when COVID-19 pandemic forces Indonesian football competition to be postponed. The government and federation already made several regulations to solve the problems around postponement. As a space for professional football players and as an organization that is equivalent to worker/labor union, APPI actively advocates on matters such as the club's responsibility towards players. Legal protection for professional football players is differentiated into two sectors, preventive and repressive. Preventive protection is a protection to prevent the dispute that could occur in the later day. Meanwhile, repressive protection in the football world is solved by non-litigation processes such as arbitration under NDRC Indonesia as an arbitrase committee under PSSI. Keywords: Legal Protection; COVID-19 Pandemic; Football Players and Football Clubs Protection; Working Relation; Lex Sportiva.AbstrakPandemi COVID-19 membawa dampak kepada banyak sektor di berbagai belahan dunia, tak terkecuali cabang olahraga sepak bola. Sebagai industri modern, hubungan antara pemain profesional dan klub profesional berupa hubungan kerja yang menghasilkan hak dan kewajiban antara kedua belah pihak yang disepakati dalam kontrak kerja. Masalah timbul tatkala pandemi COVID-19 memaksa kompetisi sepak bola Indonesia untuk dihentikan. Pemerintah dan federasi sepak bola mengeluarkan berbagai regulasi untuk mengatasi hal ini. APPI sebagai wadah pemain sepak bola profesional yang serupa dengan SP/SB secara aktif mengadvokasi kewajiban klub kepada pemain. Perlindungan hukum bagi pemain sepak bola profesional dapat dibedakan menjadi dua, yaitu preventif dan represif. Perlindungan preventif adalah perlindungan guna menanggulangi sengketa yang dapat terjadi di kemudian hari. Sementara perlindungan represif dalam olahraga diselesaikan dengan jalur non-litigasi berupa arbitrase yang diwadahi oleh NDRC Indonesia sebagai badan arbitrase di bawah PSSI.Kata Kunci: Perlindungan Hukum; Pandemi COVID-19; Perlindungan Pemain Sepak Bola dan Klub; Hubungan Kerja; Lex Sportiva.